2019
DOI: 10.17770/etr2019vol1.4129
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Quality of Freshwater Lake Sediments (Balvu and Pērkonu Lakes)

Abstract: Water quality, watershed basin and urbanization are key factors from the perspective of freshwater management; however, actual depth of waterbodies is often an overlooked element. Actual depth represents the overall depth of lake bed and depth of sediments. Some cases have been reported, where with increase of average depth of lake, it is possible to expect improvements of water quality when sediments are removed. If lakes are eutrophic, shallow, overgrown with macrophytes and contain high concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Also, Pērkonu Lake as a first lake accumulates most of the material carried with rivers. Analysis of sediments showed that they are formed mostly from vascular plants (63-78 %) [40]. Current prediction, considering the increased river runoff forecasts, expansion of macrophytes due to the increased amount of available nutrients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Pērkonu Lake as a first lake accumulates most of the material carried with rivers. Analysis of sediments showed that they are formed mostly from vascular plants (63-78 %) [40]. Current prediction, considering the increased river runoff forecasts, expansion of macrophytes due to the increased amount of available nutrients.…”
Section: Resultsmentioning
confidence: 99%
“…Previously characterized sediments of lakes [40] showed abundance of nutrients, mostly recognized as of allochthonous material from watershed basin, especially in Pērkonu Lake. Also, Pērkonu Lake as a first lake accumulates most of the material carried with rivers.…”
Section: Resultsmentioning
confidence: 99%